ANALISIS PERSEPSI AUDITOR MENGENAI FAKTOR PENENTU AUDIT FEE BERDASARKAN CLIENT ATTRIBUTES, AUDITOR ATTRIBUTES, DAN ENGAGEMENT ATRTRIBUTES - Faturachman, Aman (Jurnal Riset Akuntansi dan Keuangan, 2013)
This research purposes to know how perception auditors about determining factors of audit fee based on Client Attributes, Auditor Attributes, and Engagement Attributes at The Public Accountant Firm residing in Bandung. In this research, the indicator that is used to characterize the Client Attributes are size, complexity, inherent risk, profitability, leverage and liquidity, and industry. While the indicator to characterize the Auditor Attributes are auditorâ€™s specialization, audit tenure, and location. And the indicators to characterize the Engagement Attributes are audit problems, audit report lag, busy season, and number of reports. The Method that is used in this research is a descriptive method. The population in this research is a public accountant in Bandung. Based on sampling techniques that saturated and qualified then it take about 11 offices of public accountant. SmartPLS ver 2.0 M3 are used as a Statistical analysis. The result of this research with count the loading factor and bootstrapping method are, the first one that the perception of the auditor based on client attributes of audit fee determinants from which is very important to not important is size, complexity, profitability, inherent risk,Â  industry, and leverage liquidty, the second states that perception based on auditor attributes audit fee determinants from which is very important to not important is audit tenure, location, and specialization. And the third states that the perception of auditor engagement attributes based determinants of audit fee which is very important to not important audit report lag, busy season, audit problems and number of reports.